Upper Lip Pleomorphic Adenoma: Comparison of Reported Cases between 1990 and 2012 - Hamed Mortazavi; Somayeh Alirezaei; Saranaz Azari-Marhabi; Maryam Baharvand; Majid Eshghpour (Mashhad University of Medical Sciences, 2013)
Introduction: Pleomorphic adenoma of the upper lip is a rare entity and its diagnosis requires a high index of suspicion. The aim of this study was to review the reported cases of pleomorphic adenoma (PA) of the upper lip. Methods: This study was performed on the basis of the clinical features of 10 well-documented reported cases of the upper lip pleomorphic adenomas from 1990 to 2012 which have been indexed in the PubMed. The search strategy based on MeSH keywords included "salivary gland tumor", "salivary gland cancer", "pleomorphic adenoma", and "mixed tumor". In the clinical records the following data have been considered: Age, sex, clinical view, complaint time, site, size, texture, pathological view, treatment, recurrence rate, symptom and follow-up period. Results: Of the 11 reported cases of PA, 7 (63.7%) were female and 4 (36.3%) were male, with age ranging from 12 to 65 years. 50% of the patients were between 35 and 55 years of age. Only 3 (27.2%) of cases were younger than 20. The main clinical presentation of lesion in all cases was a submucosal nodule. There was a large interval between the first symptoms and diagnosis. The size of the lesions were between 1 and 3 cm. Involvement of the right half of the upper lip was more common than the left side. 63.6% of the lesions showed a firm consistency and bone formation was seen in one (9.09%) case. The follow-up period ranged from 5 to 48 months. There was no evidence of recurrence in any of the reported cases. Conclusion: Although rare, pleomorphic adenoma should be considered as a differential diagnosis for the swellings in the upper lip. PA has a potential for malignant transformation